FACTORS INFLUENCING EMPLOYEE PERFORMANCE : TELEWORKING, WORK-LIFE BALANCE, AND STRESS - Suryani Maryam (Sean Institute, 2023)
The COVID-19 epidemic has created a new social setting that has significantly altered how employees operate. Social exclusion and isolation have forced people to pursue teleworking. Before the COVID-19 epidemic, teleworking was regarded as a tool for boosting employment flexibility and employee liberty. This paper aims to identify how teleworking, work-life balance, stress influences employee performance. By using simple random sampling techniques, this study distributed questionnaires to 121 employees who work in private airlines in Jakarta. Partial least square offers the main statistics methodology for data analysis. The results reveal that teleworking, work-life balance and stress have significantly impact on employees’ performance amongst employee in private Airlines in Jakarta. The study implies that when organisations are willing to improve teleworking, maintain a healthy work-life balance, and reduce employee’s stress, employees' mental and physical health will improve so they tend to be more focused, energized, and productive during their working hours.